Energetyka w mieście wczoraj, dziś i jutro - Biskupski, Jacek (Public participation in urban climate policy making: The example of Lodz, 2024)
The author analyses the paths of societal participation in the energy transition in Germany and the Netherlands, comparing them to the situation in Poland. He analyses energy development in Poland, taking into account scenarios realised in Germany and the Netherlands. He describes several experiments with the application of RES in cities in these three countries, which leads to conclusions on the necessity to undertake a broad social debate on the future of energy in Poland.